In Situ Observation of Pressurized Microcrack Growth in Silicon. Issue 23 (1st August 2021) - Colonel, Lucas; Mazen, Frédéric; Landru, Didier; Kononchuk, Oleg; Ben Mohamed, Nadia; Rieutord, François
Abstract : The evolution of micrometer‐scale cracks in hydrogen‐ and helium‐implanted silicon during isothermal annealing is studied using confocal IR microscopy. Herein, it is demonstrated that the dominant mechanism of microcrack growth is crack coalescence. The coalescence of two cracks causes a sudden crack opening in silicon and leads to the formation of a larger crack. The surface of this large crack is equal to the sum of the surface areas of the two former cracks plus the opened zone. As a result, it has a less circular shape than both initial cracks. After the coalescence, the new pressurized crack surface evolves quickly and its shape circularizes again. Before their coalescence, the measurement of the distance between two microcracks reveals the increase of the gap closure velocity as two microcracks come closer due to the interaction of their stress fields. In addition, the growth of isolated cracks without coalescence due to implanted gas diffusion and crack front curvature effect on stress is detected. It is evidenced that two geometric parameters, the distance between neighboring cracks and the local curvature of the crack front, contribute to the growth of a pressurized crack. Abstract : The evolution of pressurized micrometer‐scale cracks in light‐gas‐implanted silicon upon isothermal annealing is studied in situ using confocal IR microscopy. The major changes of such crack distributions are due to crack coalescence, which is driven by local stress effects such as crack front curvature and stress amplification between neighboring cracks.